Differential N-end rule degradation of RIN4/NOI fragments generated by the AvrRpt2 effector protease - Goslin, Kevin; Naumann, Christin; Linster, Eric; Wirtz, Markus (Plant physiology, 2019)
In plants, the protein RPM1-INTERACTING PROTEIN4 (RIN4) is a central regulator of both pattern-triggered immunity and effector-triggered immunity. RIN4 is targeted by several effectors, including the Pseudomonas syringae protease effector AvrRpt2. Cleavage of RIN4 by AvrRpt2 generates potentially unstable RIN4 fragments, whose degradation leads to the activation of the resistance protein RESISTANT TO P. SYRINGAE2. Hence, identifying the determinants of RIN4 degradation is key to understanding RESISTANT TO P. SYRINGAE2-mediated effector-triggered immunity, as well as virulence functions of AvrRpt2. In addition to RIN4, AvrRpt2 cleaves host proteins from the nitrate-induced (NOI) domain family. Although cleavage of NOI domain proteins by AvrRpt2 may contribute to pattern-triggered immunity regulation, the (in)stability of these proteolytic fragments and the determinants regulating their stability remain unexamined. Notably, a common feature of RIN4, and of many NOI domain protein fragments generated by AvrRpt2 cleavage, is the exposure of a new N-terminal residue that is destabilizing according to the N-end rule. Using antibodies raised against endogenous RIN4, we show that the destabilization of AvrRpt2-cleaved RIN4 fragments is independent of the N-end rule pathway (recently renamed the N-degron pathway). By contrast, several NOI domain protein fragments are genuine substrates of the N-degron pathway. The discovery of this set of substrates considerably expands the number of known proteins targeted for degradation by this ubiquitin-dependent pathway in plants. These results advance our current understanding of the role of AvrRpt2 in promoting bacterial virulence.